Bioleaching of toxic metals from sewage sludge by co-inoculation of Acidithiobacillus and the biosurfactant-producing yeast Meyerozyma guilliermondii - Camargo, Franciele Pereira; Prado, Pierre Ferreira do [UNESP]; Tonello, Paulo Sergio [UNESP]; Dos Santos, André Cordeiro Alves; Duarte, Iolanda Cristina Silveira (Elsevier, 2018)
The aim of this research is to evaluate the influence of co-inoculation of Acidithiobacillus bacteria and the biosurfactant-producing yeast Meyerozyma guilliermondii in bioleaching processes. The tests were carried out using sewage sludge from UASB reactors co-inoculated with cultures of Acidithiobacillus and M. guilliermondii to promote the solubilization of Cd, Cr, Cu, Ni, Pb and Zn which were determined by Inductively Coupled Plasma - Optical Emission Spectrometry (ICP- OES). After 10 days of incubation, 76.5% of Zn, 59.8% of Ni, 22.0% of Cu, 9.8% of Cd, 9.8% Cr and 7.1% of Pb were solubilized. It was observed that the presence of yeast accelerated the time required for Cd solubilization from 240 to 96 h and there was a 20.1% reduction in nitrogen concentration and 7.6% for phosphorus in this assay. After the bioleaching and co-inoculation assays, the product obtained reached the maximum permissible concentrations for soil disposal for all the analyzed metals in the State of São Paulo, United States and also European Community standards.
Keywords: Glycolipid; Heavy metal; Sewage treatment